Single cell transcriptome profiling of immune tissues from germ-free and specific pathogen-free piglet - Jinwei Zhang; Chuang Tang; Yan Liu; Jing Sun; Xiaokai Li; Keren Long; Fanli Kong; Shuangshuang Chen; Hao Liang; Yuchun Ding; Mingzhou Li; Li Shen; et al. (Scientific Data)
Abstract The commensal microbiota provides immunomodulatory signals during the development, differentiation and activation of immune cells, and is crucial for maintaining host immune homeostasis. However, the systematic effects of commensal microbiota on host immunity based on large animal model at the single-cell level remain to be resolved. Here, we utilized single-cell RNA sequencing (scRNA-seq) to analyze the transcriptome profiling containing 57,720 cells from three important immune tissues [Peyer’s patches (PP), mesenteric lymph node (MLN), and spleen] of germ-free (GF) and specific pathogen-free (SPF) piglet. We presented detailed description of the dataset and preliminarily identified the major cell types including immune and non-immune cells, and further annotated the immune cell subsets. This dataset provides a data mining resource for researchers involved in microbe-host interactions, and enables in-depth analysis of cell map alterations caused by the microbiota colonization during early immune development. As the first single-cell transcriptomics dataset for immune tissue of GF and SPF piglet, this provides a valuable data resource for the study of commensal microbe-host immunity regulation.